Students' Perception of Using Webtoon Application to Enrich English Vocabulary - Gustianingsih Ika Putri; Fadly Azhar; Supriusman (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aimed to investigate the perceptions of the third-year students of the English Department Universitas Riau in using the Webtoon application to enrich English vocabulary. This research used a quantitative descriptive method approach and involved 30 students selected through purposive sampling. Data were gathered via a Likert-scale-based questionnaire distributed via WhatsApp. The findings showed a generally positive perception among students concerning the Webtoon application's usefulness, ease of use, and attitude toward using. This can be seen from the questionnaire's mean score, which reached 4.04, involving perceived usefulness (3.87), perceived ease of use (4.15), and attitude towards using (4.10). This research also found that most Webtoon application users are females, who tend to have more positive perceptions than males. In addition, students who used the free version and those who spent more time using the application showed better perceptions of vocabulary enrichment than those who used the paid version. In conclusion, third-year students of the English Department Universitas Riau positively perceive using the Webtoon application for vocabulary enrichment. They find it accessible, easy to use, and effective in enhancing their vocabulary and confidence in English through its engaging visual and narrative features.